MICROECOLOGY OF THE MONOGENEAN MEXICANA SP. ON THE GILLS OF ANISOTREMUS SCAPULARIS (TSCHUDI, 1846) (OSTEICHTHYES, HAEMULIDAE) OF THE MARINE COAST OF LIMA, PERU - Iannacone, José (2012)
The objective of this research was to evaluate the microecology of the monogenean Mexicana sp., a gill parasite of Anisotremus scapularis (Tschudi, 1846) (Haemulidae), which included: (1) determine the selectivity in relation to the prevalence (P) and numerical average abundance (AMN) to right and left (asymmetry), preference for each of the four gill arches in the host (windshear), sex and size, and (2) use of five indices of aggregation [dispersion index (DI): Variance (S2) / AMN, Green Index (Ig), Morisita index (Id), average aggregation Lloyd (m *) and the rate of aggregation patchiness or half of Lloyd (L)] of Mexicana. Twenty specimens of A. scapularis measuring 17.4 cm to 29 cm were purchased from fish market, district of Chorrillos, Lima, Peru in November 2011. Statistical package was used PASSaGE2 (Pattern Analysis, Spatial Statistical and Geographical Exegesis) to determine the values of the aggregation rates. No significant differences were observed in the Pand AMN gills of Mexicana between right and left, between the gill arches I to IV and between the sexes. P and AMN were different between the two size ranges of host fish, with a larger Pand AMN in fish greater than 25 cm. Regarding the patterns of aggregation, for Mexicana, a contagious distribution relative to its total amount, asymmetry, wind shear, sex and size of the fish. However, it was noticed that in general the rates of aggregation of Mexicana were numerically higher for the gill arch III, for females and for fish less than 25 cm. No relationship was observed between the index of dispersion (ID) on the Pand AMN of the monogenea. Mexicana is a new record for A. scapularis and Peru.